The Effect of Pagoda Leaves Extracts on the Level of IL-6 of Female Rats Induced by Staphylococcus Aureus - Fitriana Ibrahim; Prihantono Prihantono; Mardiana Ahmad; Nurul Aini Siagian (Humanistic Network for Science and Technology (HNST), 2018)
The extract of Pagoda leaves can play roles as an anti-inflammatory, antioxidant, and antibacteria. Interleukin 6 (IL-6 henceforth) is the primary mediator in responding to the inflammation, while mastitis is caused by bacteria often found in the increased level of IL-6. This research aimed to unveil the effect of giving the extracts of Pagoda leaves on the level of IL-6 of female rats (Sprague dawley therefore) induced by Staphylococcus aureus. This true experimental research employing pre-test and post-test control design used eighteen rats chosen randomly. All rats were divided into three groups, namely negative control (placebo), positive control (amoxicillin 9.6 mg/ml/kgBB/hari/oral) and treatment group (amoxicillin 9.6 mg/ml/KgBB + EDP 50 mg/ml/KgBB/hari/oral). All groups were induced by S.aureus 0.2x108 CFU. Treatment was given for five days. Investigating the level of IL6 was done using ELISA method. The data were anaylized using ANOVA formula followed by post hoc. The empirical findings showed that there was a difference in terms of the level of IL-6 in all of the groups ±24 before and after the induction of S.aureus. The result of investigating the level of IL-6 in the post-test was significant (ρ = 0.00), meaning that there was a significant difference, in which the negative control group, the level of IL-6 was insacalating; while it was dipping in both the positive and treatment groups. However, the treatment group experienced the most significant drop in terms of the level of IL-6. It can be concluded that Pagoda leaves can be used as a complementary therapy for mastitis illness caused by the S.aureus bacteria. Keywords: Interleukin 6, Mastitis, Pagoda leaves, Staphylococcus Aureus